Corporate Governance and Foreign Direct Investment - Joseph D. Alba; Donghyun Park; Peiming Wang (Asian Development Bank (ADB), 2010)
Merger and acquisition (M&A) activity is motivated by increasing shareholder value through improved corporate governance. Therefore, stronger corporate governance can reduce the returns from M&A activity, including M&A foreign direct investment (FDI). This, in turn, can reduce the returns from non-M&A FDI in light of the complementary relationship between M&A and non-M&A FDI. We use firm-level evidence to empirically examine the effect of corporate governance in the United States (US) on Japanese M&A and non-M&A FDI inflows. In doing so, we expand upon Alba, Park, and Wang (2009), which looked only at the M&A FDI inflows. We find that two landmark US corporate governance regulations help explain the sharp drop in both Japanese M&A and non-M&A FDI into the US during the 1990s. The regulations apparently encouraged US firms to improve their corporate governance. Our evidence thus suggests that corporate governance may affect both M&A and non-M&A FDI.
hdl:11540/1954
Keywords: F21; F23; G30; G34; 330; Corporate governance; FDI; merger and acquisition; Corporate Governance; Auslandsinvestition; Japanisch; USA